Spine Metastasis in Elderly: Encouraging Results for Better Survival. Issue 11 (1st June 2021) - Beaufort, Quentin; Terrier, Louis-Marie; Dubory, Arnaud; Le Nail, Louis-Romée; Cook, Ann-Rose; Cristini, Joseph; Buffenoir, Kévin; Pascal-Moussellard, Hugues; Carpentier, Alexandre; Mathon, Bertrand; Amelot, Aymeric
Abstract : Mini: The incidence of spinal metastasis (SpM) is increasing, and life expectancy for patients with malignancy is also rising. The "elderly" represent a population with steady growth in SpM proportion. Bracing is associated with lower survival. We believe that surgery should be considered, regardless of the patient's age. Study Design: Multicentric prospective study. Objective: Through this study, we aimed to clarify and update the prognostic assessment of elderly with spine metastasis (SpM). Summary of Background Data: The incidence SpM is rising, in parallel life expectancy is getting longer and the number of elderly patients presenting malignancy is increasing. Elderly patients with SpM constitute a growing heterogeneous population Methods: The patient data used in this study were obtained from a French national multicenter database of patients treated for SpM between 2014 and 2017. Two hundred and forty-three consecutive patients >70 years' old were diagnosed. Results: Median overall survival (OS) time for elderly patients following the event of SpM was 16.3 months. First, we identified significantly worse survival prognostic factors for elderly patients with SpM: poor WHO status 3/4: (hazard ratio [HR]: 2.245, 95% confidence interval [CI] 1.899–2.655; P  < 0.0001), >80 years (HR: 1.758, 95% CI 1.117–2.765; P  = 0.015) no-ambulatory neurological status (Franckel A/B status [HR: 3.219, 95% CI 1.621–6.390; P  < 0.0001)], gastrointestinal cancer (HR: 3.530, 95% CI 1.75–7.1; P  < 0.0001), lung cancer (HR: 3.452, 95% CI 1.784–6.680; P  < 0.0001), orthopedic brace treatment (HR: 1.329; 95% CI 1.050–1.683; P  = 0.018), and epiduritis (HR: 1.52, 95% CI 1.041–2.22; P  = 0.03) were independently poor prognostic factors of survival. The only good prognosis factor identified was thyroid cancer (HR: 0.257, 95% CI 0.07–0.952; P  = 0.04). Conclusion: Prognosis factors concerning the survival of elderly patients seem to be the same as those for the general population such as primary cancer histology, neurological status, WHO status, and epiduritis. Age >80 years also appears to be an independently poor prognosis factor. Our data suggest that orthopedic brace treatment is also associated with lower survival. Level of Evidence: 2